Investigation of the Blast-Induced Crack Propagation Behavior in a Material Containing an Unfilled Joint - Peng Xu; Renshu Yang; Yang Guo; Zhicheng Guo (Applied Sciences, 2020)
This study uses a dynamic caustic technique to study the crack propagation in a medium containing an unfilled joint under blasting. The results show that for the medium containing a vertical unfilled joint, the reflected dilatational wave from the joint tends to suppress both the <semantics> <msubsup> K I d </msubsup> </semantics> and the velocity of the opposite propagating crack. However, for the medium containing an oblique joint, the reflected wave from the joint increases <semantics> <msubsup> K II d </msubsup> </semantics> , and induces the opposite propagating crack deflect from its original path. Compared with the medium with a vertical joint, the wing cracks are more easy to initiate at the oblique joint where a significant stress concentration is formed under the diffraction of the blast wave. Combined with numerical results, it is found that the wing crack deflects in the clockwise direction when the shear stress was negative, and it turns to counterclockwise when the shear stress was positive.